Biology and distribution of Paphia textile in the coastal waters of Katipunan and Roxas, Zamboanga del Norte - Naguit, Maria Rio A. (The Threshold: the Official Research Journal of Jose Rizal Memorial State University, Zamboanga del Norte, 2007)
The study focused on the biology and distribution of Paphia textile, a bivalve, in the coastal waters of Katipunan at Roxas, Zamboanga del Norte. Results revealed an approximate density of about 10 clams/m2 in the aforementioned areas. Morphological comparisons showed that clams which are 5-7 years old have the same lengths while the 8-9 years old clams have longer lengths. Clam weights positively correlated with clam lengths. The ages of the clams can be inferred from their lengths and rings.